The image of a falcon chained to constant luck - Mohichehra Rustamova (Genius Journals, 2022)
When Matnazar Abdulhakim and his friend Jumanazar aka went to Urgench airport, he saw his friend Matnazar Abdulhakim on the plane at the entrance and asked him to write a poem about the plane. Matnazar Abdulhakim skillfully summarizes his experiences in the verses under the name "Falcon on the Podium" while looking at the plane.
Keywords: Muztar; skill; rock band; good luck